2016
DOI: 10.3847/0004-637x/828/1/23
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transients on Photospheric and Chromospheric Power Distributions

Abstract: We have observed a quiet-Sun region with the Swedish 1 m Solar Telescope equipped with the CRISP Imaging SpectroPolarimeter. High-resolution, high-cadence, Hα line scanning images were taken to observe different layers of the solar atmosphere from the photosphere to upper chromosphere. We study the distribution of power in different period bands at different heights. Power maps of the upper photosphere and the lower chromosphere show suppressed power surrounding the magnetic-network elements, known as "magneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
2
4
0
Order By: Relevance
“…using a double Voigt model), then the resulting Doppler velocities inferred from the emission Voigt fit are shown in the right panel of figure 7. In particular, it can be seen in the right panel of figure 7 that many of the derived Doppler velocities associated with dynamic phenomena appear to rapidly change between neighbouring pixels, an effect that has been documented in previous velocity studies of the solar chromosphere [58][59][60]. These rapid velocity excursions appear to be closely linked to instances when the Ca II 8542 Å line goes into emission.…”
Section: Proof Of Concept Testing With Ibis Datasupporting
confidence: 61%
“…using a double Voigt model), then the resulting Doppler velocities inferred from the emission Voigt fit are shown in the right panel of figure 7. In particular, it can be seen in the right panel of figure 7 that many of the derived Doppler velocities associated with dynamic phenomena appear to rapidly change between neighbouring pixels, an effect that has been documented in previous velocity studies of the solar chromosphere [58][59][60]. These rapid velocity excursions appear to be closely linked to instances when the Ca II 8542 Å line goes into emission.…”
Section: Proof Of Concept Testing With Ibis Datasupporting
confidence: 61%
“…The pronounced 3-min fluctuations have often been observed in the line-of-sight velocity and/or intensity signals, in both quiet and active regions, through chromospheric spectral lines such as Ca II H & K [27][28][29][30], Ca II infrared triplet [30][31][32][33], Hα [34], He I 1083 nm [28,35,36] and Mg II h & k [37]. In the quiet Sun, while the 3-min oscillations have been shown in many observations of the low-to-mid chromosphere (or using relatively broad-band filters), a lack of such fluctuations in intensity image sequences of Hα line-core observations have also been reported [38]. Samanta et al [38] showed, however, that the dominating 3-min oscillations could be detected in the line-of-sight velocities of their Hα observations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the quiet Sun, while the 3-min oscillations have been shown in many observations of the low-to-mid chromosphere (or using relatively broad-band filters), a lack of such fluctuations in intensity image sequences of H α line-core observations have also been reported [38]. Samanta et al [38] showed, however, that the dominating 3-min oscillations could be detected in the line-of-sight velocities of their H α observations (i.e. also at the same spectral line position; the H α line-core), but not in the intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In the quiet Sun, while the 3-min oscillations have been shown in many observations of the low-to-mid chromosphere (or using relatively broad-band filters), a lack of such fluctuations in intensity image sequences of Hα line-core observations have also been reported [38]. Samanta et al [38] showed, however, that the dominating 3-min oscillations could be detected in the line-of-sight velocities of their Hα observations (i.e., also at the same spectral line position; the Hα line-core), but not in the intensity. In the latter, they found the dominant periods (in the entire field-of-view) to be longer than five minutes.…”
Section: Introductionmentioning
confidence: 91%
“…The pronounced 3-min fluctuations have often been observed in the line-of-sight velocity and/or intensity signals, in both quiet and active regions, through chromospheric spectral lines such as Ca II H & K [27][28][29][30], Ca II infrared triplet [30][31][32][33], Hα [34], He I 1083 nm [28,35,36], and Mg II h & k [37]. In the quiet Sun, while the 3-min oscillations have been shown in many observations of the low-to-mid chromosphere (or using relatively broad-band filters), a lack of such fluctuations in intensity image sequences of Hα line-core observations have also been reported [38]. Samanta et al [38] showed, however, that the dominating 3-min oscillations could be detected in the line-of-sight velocities of their Hα observations (i.e., also at the same spectral line position; the Hα line-core), but not in the intensity.…”
Section: Introductionmentioning
confidence: 99%